High intensity impact of granular matter with edge-clamped ductile plates. (January 2018) - Kyner, Anne; Dharmasena, Kumar; Williams, Keith; Deshpande, Vikram; Wadley, Haydn N.G.
Highlights: The out of plane displacement of edge restrained, stainless plates has been measured following impact by spherical shells of water saturated silica or higher density zirconia particles at velocities of 500–1200 m/s. The radial expansion of the spherical shells was observed using high-speed video techniques while the impact pressure and transmitted impulse were measured using a Kolsky bar. A discrete particle-based simulation code predicted particle front positions, velocities, impact pressures, and plate deformations that agreed well with measurements. The study confirmed a recently proposed linear scaling of the plates out of plane displacement with incident impulse, andexperimentally identified the existence of an instability at the leading edge of the fastest expanding granular shells. Abstract: The deformation of ductile square stainless steel plates during central impact by high velocity, spherically symmetric granular particle shells has been investigated using an approach that combined large-scale experiments with numerical simulation. The study used suspended spherical explosive charges to accelerate 25–150 kg concentric shells of water saturated glass or higher density zirconia particles to velocities of 500–1200 m/s. The test charges were positioned above the center of 2.54 cm thick, 1.32 m × 1.32 m wide edge clamped panels made of 304 stainless steel, and their permanent deflection fields measured after testing. A novel edge restraint approach was utilized to avoid disruption of reflected particle flow over the impacted surface of the sample and so avoid plate failure near the gripped regions. The end of a Kolsky bar was positioned at a location symmetrically equivalent to the plate center, and was used to measure both the pressure and the specific impulse applied to the plate center. The evolution of the granular shell topology following charge detonation was characterized by analysis of high-speed video images. The radial expansion of the granular shells, the pressure and impulse that they transferred to the Kolsky bar, and the test plates out-of-plane displacement field were all well predicted by a discrete particle-based simulation approach. The study confirms earlier simplified model estimates of an approximately linear dependence of the plates out-of-plane displacement upon incident impulse, and validates the use of the edge restraint concept. It also experimentally identifies the existence of a granular shell velocity dependent instability at the leading edge of the fastest expanding granular shells.